CITRA PEREMPUAN INDONESIA MASA JEPANG PADA DUA CERPEN DALAM MAJALAH PANDJI POESTAKA (The Image of Indonesian Women on Japanese Period in Two Short Stories in Pandji Poestaka Magazine) - Hanifa Widyas Sukma Ningrum; Sunu Wasono (SAWERIGADING, 2023)
The image of women is an impression that arises as a result of individual knowledge and experience that is presented implicitly through literary works. Periodization of literary works can also present images of women who represent certain characteristics. “Isteri Tabib” by Teha and “Putri Pahlawan Indonesia” by N. St. Iskandar are two short stories published in Pandji Poestaka during the Japanese occupation of Indonesia. This research will discuss the image of Indonesian women during the Japanese period presented through these two short stories. The purpose of this study is to reveal that image of Indonesian women more or less shaped by the intervention of the Japanese. The research method used is a qualitative approach to the close reading.  Data collection techniques use by reading the corpus repeatedly and then marking the narratives and dialogues between characters related to the image of women. The results and analysis revealed that the image of Indonesian women during the Japanese occupation was the image of a wife which was closely related to the domestic sphere, the image of a mother, and the image of a woman warrior. These three images exist as a form of propaganda to create an ideal woman who is useful for the interests of Japanese ideals.AbstrakCitra perempuan merupakan kesan yang muncul sebagai hasil dari pengetahuan dan pengalaman individu yang dihadirkan secara implisit melalui karya sastra. Periodisasi karya sastra juga dapat menghadirkan citra perempuan yang mewakili ciri tertentu. “Isteri Tabib” karya Teha dan “Putri Pahlawan Indonesia” karya N. St. Iskandar merupakan dua cerpen yang terbit di majalah Pandji Poestaka saat masa pendudukan Jepang di Indonesia. Penelitian ini akan membahas citra perempuan Indonesia masa Jepang yang dihadirkan melalui dua cerpen tersebut. Tujuan penelitian ini adalah mengungkapkan citra perempuan Indonesia sedikit banyak dibentuk oleh campur tangan pihak Jepang. Metode penelitian yang digunakan adalah pendekatan kualitatif metode close reading. Adapun teknik pengumpulan data dilakukan dengan cara pembacaan korpus secara berulang kemudian menandai narasi dan dialog antartokoh yang berkaitan dengan citra perempuan. Hasil dan analisis mengungkapkan citra perempuan Indonesia di masa pendudukan Jepang adalah citra seorang istri yang erat berkaitan dengan ranah domestik, citra ibu, serta citra perempuan pejuang. Ketiga citra tersebut hadir sebagai bentuk propaganda untuk menciptakan perempuan ideal yang berguna untuk kepentingan cita-cita Jepang.